Cow's Milk and Dairy Consumption: Is There Now Consensus for Cardiometabolic Health? - Poppitt, Sally D. (Frontiers in Nutrition, 2020)
Cow’s milk and dairy products derived from this complex food source have long been proposed as beneficial to human health, yet underlying clinical evidence of direct benefit continues to raise controversy. Evidence underpins some positive cardiometabolic effects of a number of dairy macro- and micronutrient components including whey protein and casein, medium-chain, odd-chain and unsaturated fats, milk fat globule membrane (MFGM) and polar phospholipids, vitamin D, and calcium, in addition to non-bovine components including bacterial and yeast probiotics. More controversial remain lipid components trans fats, including trans vaccenic acid, trans palmitoleic acid and conjugated cis trans linoleic acid (CLA). New evidence is rapidly identifying multiple pathways by which these dairy nutrients may effect health. Processing, fermentation and homogenization may also have positive effects. Conversely, the high saturated fat content of dairy has long raised concern, aligned with international guidelines to minimize dietary intake of animal-origin saturated fatty acids (SFA) to achieve better cardiometabolic health. However, led in part by observational studies and meta-analyses showing dairy to have no or even an inverse association with cardiometabolic health, evidence from randomized controlled trials has been scrutinized over the last 5 years, and focus on low-fat dairy has been challenged. Recent evidence supports the hypothesis that adverse effects of SFAs on metabolic health may be ameliorated when these fats are consumed within a complex matrix such as milk, cheese or yogurt. Dairy food categories may influence outcomes as much as total fat content. For example, yogurt and high-fat, high-SFA cheese have a negative association with risk of type 2 diabetes (T2D) in many, not all, published trials. Further clinical studies are required before outcomes can be confirmed and supported through dietary guidelines. Current advisories from national guidance groups such as American Heart Association (AHA) and European Society of Cardiology (ESC) continue to promote consumption of low-fat dairy products, whilst liquid milk and yogurt remain part of nutrition guidelines from joint American Diabetes Association (ADA)/European Association for Study of Diabetes (EASD) reports, and as part of a “no-one-size-fits-all” answer to diet and T2D by the ADA in their most recent 2019 Consensus Report.